Adjunct n-3 Long-Chain Polyunsaturated Fatty Acid Treatment in Tuberculosis Reduces Inflammation and Improves Anemia of Infection More in C3HeB/FeJ Mice With Low n-3 Fatty Acid Status Than Sufficient n-3 Fatty Acid Status - Hayford, Frank E. A.; Dolman, Robin C.; Ozturk, Mumin; Nienaber, Arista; Ricci, Cristian; Loots, Du Toit; Brombacher, Frank; Blaauw, Renée; Smuts, Cornelius M.; Parihar, Suraj P.; Malan, Linda (Frontiers in Nutrition, 2021)
Some vulnerable population groups at risk for tuberculosis (TB) may have a low n-3 polyunsaturated fatty acid (PUFA) status. Our research previously showed that adjunct n-3 LCPUFA in TB are beneficial in n-3 PUFA sufficient C3HeB/FeJ mice. Here we investigated the effect of adjunct n-3 LCPUFA supplementation to TB-mice with a low, compared to a sufficient n-3 PUFA status. Mice were conditioned on an n-3 PUFA-deficient (n-3FAD) or n-3 PUFA-sufficient (n-3FAS) diet for six weeks prior to Mycobacterium tuberculosis (Mtb) infection. At two weeks post-infection, both groups were switched to an n-3 LCPUFA (EPA/DHA) supplemented diet and euthanised at 4- and 14- days post-treatment. Iron and anaemia status, bacterial loads, lung pathology, lung cytokines/chemokines and lung lipid mediators were measured. Haemoglobin (Hb) levels (p = 0.009) and liver iron (p = 0.051) were higher in the n-3FAD group, when compared to the n-3FAS group 14 days after EPA/DHA supplementation. Furthermore, our results show reduced levels of pro-inflammatory lung cytokines; IL-6 (p = 0.011), IL-1α (p = 0.039), MCP1 (p = 0.003), MIP1- α (p = 0.043) and RANTES (p = 0.034), and higher anti-inflammatory cytokine IL-4 (p = 0.002) and growth factor GMCSF (p = 0.007) in the n-3FAD compared to the n-3FAS TB-mice group after 14 days. These results suggest that supplementing low n-3 PUFA status may lead to improved mitigation of TB-induced anaemia. Furthermore, the low n-3 fatty acid status TB mice supplemented with n-3 LCPUFA showed comparatively improved inflammation – albeit a reduced pro-resolving lipid mediator effects.